Charge carrier dynamics in a ternary bulk heterojunction system consisting of P3HT, fullerene, and a low bandgap polymer - Koppe, Markus; Egelhaaf, Hans-Joachim; Clodic, Ewan; Morana, Mauro; Lueer, Larry; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Ameri, Tayebeh; Brabec, Christoph (Advanced Energy Materials, 2013)
The photoresponse of P3HT:PC BM based organic solar cells can be enhanced by blending the bulk heterojunction with the low band gap polymer Si-PCPDTBT. Organic solar cells containing the resulting ternary blend as the photoactive layer deliver short circuit currents of up to 15.5 mA cm. Morphological studies show modest phase separation without the perturbation of the crystallinity of the P3HT:PC BM matrix, in accordance with the measured acceptable fill factors. Picosecond time-resolved pump-probe spectroscopy reveals that the sensitization of P3HT:PC BM with Si-PCPDTBT involves the transfer of photogenerated positive polarons from the low band gap polymer to P3HT within few hundreds of picoseconds. Intensity dependent experiments in combination with global fitting show that the charge transfer from Si-PCPDTBT to P3HT competes with non-geminate charge carrier recombination of the holes in the Si-PCPDTBT phase with electrons in the PC BM phase, both processes being of diffusive nature. At excitation densities corresponding to steady state conditions under one sun, modelling predicts hole transfer efficiencies exceeding 90%, in accordance with IQE measurements. At higher pump intensities, bimolecular recombination suppresses the hole transfer process effectively. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.